Respuestas

2013-04-24T21:27:34+02:00

[(x+2)^2] /2 - [x^2] /4 = [(x+3)(x-2)] / 2+1

[x^2 +4] /2 - [x^2] /4 = [(x+3)(x-2)] / 3

[(2x^2 +8) - (x^2)] / 4 = [x^2-2x+3x-6] / 3

[x^2 + 8] /4 = [x^2 +x -6] /3

3[x^2 + 8] = 4 [x^2 +x -6]

3x^2 + 24 = 4x^2 +4x - 24

0= x^2 +4x -48

(x+) (x-)=0 ::::::::::::::::::::: no me dio

 

lo hare por ecucion cuadratica

a=1  b=4   c= -48

 

x= -(4) +- raiz/ [(4)^2 - 4 (1) (-48)]    / 2(1)

x= -4 +- raiz/ [6 +192]   / 2

x= [-4 +- 14.0713] /2     :::::::::::::::::::::::::::: el valor de la raiz es aproximado

 

x1=[-4 +14.0713] /2 = 10.0713 /2 = 5.03565

x2=[-4 -14.0713] /2 = -18.0713 /2 = -9.03565

 

aam....... hay lo tienes